2020
DOI: 10.1002/slct.201902776
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances and Prospects in the Tishchenko Reaction

Abstract: Tishchenko reaction is the dimerization of two molecules of an aldehyde to produce symmetrical esters. These esters find wide applications in many reactions in organic synthesis. A variant of this reaction, the Evans‐Tishchenko reaction, catalyzed by SmI2 affords 1,3‐anti‐diol monoesters. This chemistry has found wide applications in natural product synthesis as it offers a mild and efficient methodology for the formation of 1,3‐diols stereoselectively. In this review, we mainly focus on recent advancements in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 88 publications
0
11
0
Order By: Relevance
“…The Tishchenko reaction (or the Claisen–Tishchenko reaction), which has been known for more than a century, is a most atom-efficient and waste-free strategy to synthesize symmetric carboxylic esters by the dimerization of aldehydes . To date, a number of metal catalysts including aluminum alkoxides, alkali and alkaline earth metal oxides, transition metals, and actinide complexes have been developed for this reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Tishchenko reaction (or the Claisen–Tishchenko reaction), which has been known for more than a century, is a most atom-efficient and waste-free strategy to synthesize symmetric carboxylic esters by the dimerization of aldehydes . To date, a number of metal catalysts including aluminum alkoxides, alkali and alkaline earth metal oxides, transition metals, and actinide complexes have been developed for this reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The Tishchenko reaction (or the Claisen−Tishchenko reaction), which has been known for more than a century, is a most atom-efficient and waste-free strategy to synthesize symmetric carboxylic esters by the dimerization of aldehydes. 16 To date, a number of metal catalysts including aluminum alkoxides, 17 alkali and alkaline earth metal oxides, 18 transition metals, 19 and actinide complexes 20 have been developed for this reaction. To the best of our knowledge, a limited number of rare-earth metal complexes are proven to be useful in the dimerization of aldehydes, such as and the low efficiency in the case of heteroaromatic and aliphatic aldehydes limited their further application.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Known for about 130 years, the Tishchenko reaction has been viewed as a promising candidate for a universal, atom efficient method of preparing esters, though it has long been plagued with selectivity issues when combining two distinct aldehyde species, with four possible products from each two‐aldehyde combination [99–101] . Catalysis of this reaction by Lewis acids and transition metals has been well documented, and recently its scope has been expanded to include several s‐block metal catalysts, which show that this method of ester formation can also be carried out by simple alkali metal tert ‐butoxides, hydrides or amides [102–104] . Relevant to the research reported herein is that among these new main group Tishchenko catalysts is work by Hill showing alkaline earth metal pre‐catalysts bearing NacNac ligands [105] .…”
Section: Resultsmentioning
confidence: 99%
“…Given that the initial molar ratio of methanol to ethanol in the prereaction mixture is 14.4:1, it appears that the specific mixture of solid carboxylate formed is simply a function of the molar ratio of starting alcohols. Such solids are well-known as side products in Guerbet catalysis (even if they are not always reported) and form via the Cannizzaro or Tishchenko reaction from formaldehyde or acetaldehyde. , Any formate produced can be further dehydrogenated to sodium carbonate, which is detected by 13 C NMR spectroscopy. This dehydrogenation also produces hydrogen, which leads to a buildup of pressure within the autoclave over the course of the reaction. , It seems that this rhenium catalyst has a particular propensity to form such solids in comparison to analogous manganese or ruthenium catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…Such solids are well-known as side products in Guerbet catalysis (even if they are not always reported) and form via the Cannizzaro or Tishchenko reaction from formaldehyde or acetaldehyde. 33,34 Any formate produced can be further dehydrogenated to sodium carbonate, which is detected by 13 C NMR spectroscopy. This dehydrogenation also produces hydrogen, which leads to a buildup of pressure within the autoclave over the course of the reaction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%